Toenail concentrations of trace elements and occupational history in pancreatic cancer. (June 2019) - Camargo, Judit; Pumarega, José A.; Alguacil, Joan; Sanz-Gallén, Pere; Gasull, Magda; Delclos, George L.; Amaral, André F.S.; Porta, Miquel
Abstract: Background: Some occupations potentially entailing exposure to cadmium, arsenic, lead, selenium, nickel, and chromium have been associated with an increased risk of exocrine pancreatic cancer (EPC), but no studies have assessed whether body concentrations of such compounds differed among subjects occupationally exposed and unexposed. No studies which found that exposure to such metals increased the risk of EPC assessed whether past occupations were the source of exposure. Objective: The aim was to analyse the relationship between toenail concentrations of trace elements and occupational history in EPC patients. Methods: The study included 114 EPC cases personally interviewed on occupational history and lifestyle factors. Occupations were coded according to the International Standard Classification of Occupations 1988. Selected occupational exposures were assessed by two industrial hygienists and with the Finnish job-exposure matrix (Finjem). Concentrations of 12 trace elements were determined in toenail samples by inductively coupled plasma mass spectrometry. Adjusted geometric means (aGMs) and 95% confidence intervals (95% CI) were calculated. Results: Patients occupationally exposed to aromatic hydrocarbon solvents (AHs) had higher concentrations of cadmium, manganese, lead, iron and vanadium. The aGM of cadmium concentrations for cases exposed to any pesticide was 0.056 μg/g [95% CI: 0.029–0.108], and, for unexposed cases, 0.023 μg/g [0.017–0.031]. Patients occupationally exposed to pesticides had higher concentrations of cadmium and manganese. Higher concentrations of vanadium, lead and arsenic were related to exposure to formaldehyde. Vanadium and lead were also associated with exposure to chlorinated hydrocarbon solvents, and arsenic was related to exposure to polycyclic aromatic hydrocarbons (PAHs). Conclusions: Patients occupationally exposed to AHs, pesticides, chlorinated hydrocarbon solvents, formaldehyde, volatile sulphur compounds and PAHs had higher concentrations of several metals. These elements may account for some of the occupational risks previously reported for pancreatic cancer. Highlights: Concentrations of cadmium and manganese were higher in patients with pancreatic cancer exposed to pesticides Cadmium, manganese, lead, iron and vanadium were higher in patients with pancreatic cancer exposed to aromatic hydrocarbons Vanadium and lead were higher in patients exposed to chlorinated hydrocarbon solvents and to formaldehyde Arsenic was higher in patients exposed to formaldehyde and to polycyclic aromatic hydrocarbons Trace elements may explain some occupational risks previously observed for pancreatic cancer